HUMAN RESOURCE DEVELOPMENT STRATEGY IN ISLAMIC EDUCATIONAL INSTITUTIONS - Aminullah, Sahlan Muhammad; Rindaningsih, Ida (Journal of Economic and Economic Policy, 2024)
General Background: Human Resources (HR) are vital for the sustainability of educational institutions, serving as a critical factor in achieving educational goals. Specific Background: With the rapid changes in society and values, the need for high-quality HR has become increasingly pronounced, particularly in Islamic education where the teachings of Islam guide human development. Knowledge Gap: Research on effective management practices in education that align with Islamic principles, especially in the continuous development of educators, is limited. Aims: This study aims to explore the significance of effective human resource management in enhancing the quality of education in Islamic institutions, focusing on the development of educators and their adherence to Islamic values. Results: Through qualitative descriptive research involving interviews, observations, and documentation, findings reveal that robust HR management practices significantly improve educators' competencies, which in turn positively influence student outcomes and institutional effectiveness. Novelty: This research contributes new insights into the intersection of HR management and Islamic educational values, emphasizing the necessity for educators to adapt to contemporary challenges while remaining grounded in Islamic teachings. Implications: The findings underscore the importance of ongoing professional development for educators, suggesting that institutions prioritize HR strategies that foster alignment with Islamic principles to ensure sustainable educational success. The study also highlights the need for further exploration into the long-term impacts of these HR initiatives on student performance and the overall educational landscape in various Islamic contexts.